HELLP SYNDROME AND RUPTURE OF HEPATIC SUBCAPSULAR HEMATOMA: A CASE REPORT - Olivencia, Claudia (2015)
A case of hepatic rupture is presented in a primigravida 31 years, who presented cesarean delivery for fetal death and then died, despite therapeutic measures put in place. A review of current knowledge on this complication of HELLP syndrome is made.